Nanocellulose bio-based composites for food packaging - Soares da Silva, F. A. G. (2020)
The food industry is increasingly demanding advanced and eco-friendly sustainable packaging materials with improved physical, mechanical and barrier properties. The currently used materials are synthetic and non-degradable, therefore raising environmental concerns. Consequently, research efforts have been made in recent years towards the development of bio-based sustainable packaging materials. In this review, the potential of nanocelluloses as nanofillers or as coatings for the development of bio-based nanocomposites is discussed, namely: (i) the physico-chemical interaction of nanocellulose with the adjacent polymeric phase, (ii) the effect of nanocellulose modification/functionalization on the final properties of the composites, (iii) the production methods for such composites, and (iv) the effect of nanocellulose on the overall migration, toxicity, and the potential risk to human health. Lastly, the technology readiness level of nanocellulose and nanocellulose based composites for the market of food packaging is discussed.